Behavior and Activity Patterns of Smooth-coated Otters (Lutrogale perspicillata) in Shuklaphanta National Park, Nepal - Awasthi, Balram; Uprety, Kusum; Shrestha, Purna Man; Banjade, Babu Ram; Yoxon, Grace M; Kunwar, Amar (Journal of Institute of Science and Technology, 2024)
Understanding the behavior and activity patterns of Smooth-coated Otters (Lutrogale perspicillata) is essential for their conservation and management, particularly within protected areas such as Shuklaphanta National Park, Nepal. Therefore, we employed camera traps to monitor otter behavior and activity patterns in Shuklaphanta National Park. We observed the majority of otter activities during daylight hours, with a peak in activity occurring between 07:00 to 09:00 hours and 11:00 to 13:00 hours. Smooth-coated Otters displayed heightened activity during the early morning, possibly associated with foraging or territorial behaviors. Common behaviors observed included alertness, scent-marking and latrines, and walking. These findings reveal that camera traps offer a novel and effective method for monitoring otter behavior in the wild. Camera traps proved particularly advantageous in river sections with dense vegetation, enabling continuous monitoring and overcoming logistical challenges. Our study underscores the importance of prioritizing behavior, activity patterns, and individual identification research to enhance conservation efforts. Given the threats posed by human-altered landscapes, understanding otter behavior is paramount for formulating effective management and conservation strategies, particularly in protected areas like Shuklaphanta National Park, Nepal.